Intraperitoneal Steroid Therapy for Recurrent Malignant Ascites in Advanced Cancer Patients: A Case Series - Nashid Islam; Jheelam Biswas; Shima Rani Sarker; Salma Ahsan Khanam (Clinical Case Reports)
ABSTRACT Intraperitoneal administration of depot corticosteroids following an initial paracentesis reduces ascitic fluid formation and extends the interval between subsequent paracentesis sessions. This approach may effectively manage recurrent malignant ascites and enhance patients' quality of life.